Controlled Growth of Platinum Nanowire Arrays on Sulfur Doped Graphene as High Performance Electrocatalyst - Wang, Rongyue; Higgins, Drew C.; Hoque, Md Ariful; Lee, DongUn; Hassan, Fathy; Chen, Zhongwei (Scientific reports, 2013)
Graphene supported Pt nanostructures have great potential to be used as catalysts in electrochemical energy conversion and storage technologies; however the simultaneous control of Pt morphology and dispersion, along with ideally tailoring the physical properties of the catalyst support properties has proven very challenging. Using sulfur doped graphene (SG) as a support material, the heterogeneous dopant atoms could serve as nucleation sites allowing for the preparation of SG supported Pt nanowire arrays with ultra-thin diameters (2–5 nm) and dense surface coverage. Detailed investigation of the preparation technique reveals that the structure of the resulting composite could be readily controlled by fine tuning the Pt nanowire nucleation and growth reaction kinetics and the Pt-support interactions, whereby a mechanistic platinum nanowire array growth model is proposed. Electrochemical characterization demonstrates that the composite materials have 2–3 times higher catalytic activities toward the oxygen reduction and methanol oxidation reaction compared with commercial Pt/C catalyst.